Removal of reactive anionic dyes from binary solutions by adsorption onto quaternized kenaf core fiber - Tharwani, Intidhar Jabir Idan; Md. Jamil, Siti Nurul Ain; Abdullah, Luqman Chuah; Choong, Thomas Shean Yaw (Hindawi Publishing Corporation, 2017)
The most challenging mission in wastewater treatment plants is the removal of anionic dyes, because they are water-soluble and produce very shining colours in the water. In this regard, kenaf core fiber (KCF) was chemically modified by the quaternized agent(3-chloro-2-hydroxypropyl) trimethylammonium chloride to increase surface area and change the surface properties in order to improve the removing reactive anionic dyes from binary aqueous solution. The influencing operating factors like dye concentration, pH, adsorbent dosage, and contact time were examined in a batch mode. The results indicate that the percentage of removal of Reactive Red-RB (RR-RB) and Reactive Black-5 (RB-5) dyes from binary solution was increased with increasing dyes concentrations and the maximum percentage of removal reached up to 98.4% and 99.9% for RR-RB and RB-5, respectively. Studies on effect of pH showed that the adsorption was not significantly influenced by pH. The equilibrium analyses explain that, in spite of the extended Langmuir model failure to describe the data in the binary system, it is better than the Jain and Snoeyink model in describing the adsorption behavior of binary dyes onto QKCF. Also, the pseudo-second-order model was better to represent the adsorption kinetics for RR-RB and RB-5 dyes on QKCF.